Right ventricular enlargement predicts responsiveness to tolvaptan in congestive heart failure patients with reduced ejection fraction. (December 2018) - Nonin, Shinichi; Iwata, Shinichi; Ito, Asahiro; Tamura, Soichiro; Kitada, Ryoko; Kawai, Yu; Ishikawa, Sera; Doi, Atsushi; Hanatani, Akihisa; Yoshiyama, Minoru
Abstract: Background: Tolvaptan is a vasopressin type 2 receptor antagonist used in heart failure (HF) with refractory diuretic resistance. However, since tolvaptan is also ineffective in some HF patients with reduced ejection fraction (HFrEF), the identification of responders is important. Methods: The study population consisted of 51 HFrEF patients who were administered tolvaptan (EF, 28 ± 7%). We defined responders as patients with a ≥50% increase in urine volume during the 24-hours after administration of tolvaptan. All patients underwent comprehensive transthoracic echocardiography before administration of tolvaptan. Patients were followed for 120 days to ascertain secondary events (cardiac death and rehospitalization for HF). Results: Multiple regression analysis indicated that right ventricular (RV) enlargement (defined as basal RV diameter > 41 mm and midlevel RV diameter > 35 mm, according to guidelines) remained a predictor of response after adjustment for age, sex, starting dosage of tolvaptan, and estimated glomerular filtration rate (odds ratio, 4.88; 95%-confidence interval, 1.26–18.9; P < 0.05), whereas left ventricular parameters and RV dysfunction were not. Kaplan-Meier curves indicated responsiveness to tolvaptan was associated with better prognosis among the overall population ( P < 0.05); similar trends were observed among patients with RV dilatation ( P = 0.056). Conclusions: These findings suggest that RV enlargement, which represents right-sided volume overload, elevated filling pressure, and diastolic dysfunction similar to that seen in constrictive pericarditis, predicts responsiveness to tolvaptan in patients with HFrEF. Moreover, administration of tolvaptan may have the potential to improve the reportedly poor prognosis for HFrEF patients with RV dilatation.